Escalated oxycodone self-administration is associated with expression of voltage gated and calcium activated potassium channels in the mesocorticolimbic system in rats - Wabreha, Ammanuel Y.; Adjei, Nasser; Ladenheim, Bruce; Cadet, Jean Lud; Daiwile, Atul P. (Frontiers in Pharmacology, 2025)
BackgroundThe number of individuals diagnosed with opioid use disorder (OUD) has risen steeply because of increased prescribing of opioid drugs including oxycodone for chronic pain relief. When rats given extended access to oxycodone only a subset of animals self-administers more drug over time. Identifying the molecular mechanism associated with this behavior can introduce novel ways to combat OUD. Herein, we sought to identify the alteration in the expression of voltage gated and calcium activated potassium channels after extended access to oxycodone self-administration.MethodsWe used male Sprague-Dawley rats that self-administered oxycodone for 20 days according to short-access (ShA, 3 h per day) and long-access (LgA, 9 h per day) paradigms.ResultsLgA rats escalated their oxycodone intake and developed into two phenotypes, named long-access high (LgA-H, escalated intake) and long-access low (LgA-L, non-escalated intake) rats, based on the quantities of oxycodone intake during the self-administration experiment. ShA rats maintained similar oxycodone intake throughout 20 days of self-administration. Rats were euthanized 2 h after the last self-administration session and their prefrontal cortex (PFC), nucleus accumbens (NAc), and hippocampus (HIP) were dissected out for gene expression analysis. Given the relationship between potassium channels and substance use disorder we performed gene expression analysis for voltage and calcium activated potassium channels. The expression of potassium channels in oxycodone self-administered rats was found to be brain region dependent. Specifically, LgA-H rats displayed increased expression of Kcnd2, Kcnd3, Kcng2 and Kcnt1 in their NAc. In the PFC, LgA-L group showed higher mRNA levels for Kcna3, Kcna4, Kcnd3, Kcnq4, Kcnq5, Kcnma1 and Kcnn2. Finally, Kcna5, Kcna10, Kcng1, Kcnn1 and Kcnn2 found to be upregulated in the HIP of ShA rats.ConclusionOur observation is of significant translational importance providing further support that targeting potassium channel can lead to development of better therapeutic approaches against OUD in humans.